Mastering Adobe Captivate 2017 : create professional SCORM-compliant eLearning content with Adobe Captivate /: create professional SCORM-compliant eLearning content with Adobe Captivate. (2017) - Jaisingh, Pooja; Bruyndonckx, Damien
No abstract available